Enhancing Arabic Translation Competency In Higher Education: An Evaluation Of The Becoming A Translation Practitioner' Program/ تعزيز مهارات الترجمة للغة العربية في التعليم العالي: تقييم برنامج أن تصبح ممارسًا للترجمة - Baihaqi, M; Syarifah, Ainun; Arif, Muthahir (Ijaz Arabi Journal of Arabic Learning, 2025)
This study aims to evaluate the effectiveness of the "Becoming a Translation Practitioner" program organized by the Lisan Arabi Centre for Translation in improving translation competencies among higher education students. The program was designed with a project-based approach to address the gap between academic training and the demands of the translation industry. Involving 60 students from UIN Sunan Ampel Surabaya and UIN Raden Fatah Palembang. this research employed a mixed-method approach, including interviews, observations, and document analysis. The findings revealed a significant improvement in participants' translation competencies, as indicated by an increase in the average scores from 67.2 (pre-test) to 82.4 (post-test). The program enabled participants to produce final products in the form of ISBN-standard books, demonstrating their practical translation skills. The challenges, such as limited vocabulary and time constraints, were identified; however, participants generally provided positive feedback regarding the program's impact on their career readiness as professional translators. The study concludes that a project-based approach, supported by integrating technology and guidance from experienced practitioners, can effectively enhance translation competencies. These findings serve as an essential reference for developing similar training programs in other institutions to meet the evolving needs of the translation industry. This research contributes to developing innovative training models in higher education by integrating practical approaches and technology to enhance the relevance and competitiveness of graduates in the job market.